Ectopic expression of S28A-mutated Histone H3 modulates longevity, stress resistance and cardiac function in Drosophila - Joos, Julius P.; Saadatmand, Ali R.; Schnabel, C.; Viktorinová, I.; Brand, T.; Kramer, M.; Nattel, S.; Dobrev, D.; Tomancak, Pavel; Backs, Johannes; Kleinbongard, P.; Heusch, G.; et al. (Scientific reports, 2018)
Histone H3 serine 28 (H3S28) phosphorylation and de-repression of polycomb repressive complex (PRC)-mediated gene regulation is linked to stress conditions in mitotic and post-mitotic cells. To better understand the role of H3S28 phosphorylation in vivo, we studied a Drosophila strain with ectopic expression of constitutively-activated H3S28A, which prevents PRC2 binding at H3S28, thus mimicking H3S28 phosphorylation. H3S28A mutants showed prolonged life span and improved resistance against starvation and paraquat-induced oxidative stress. Morphological and functional analysis of heart tubes revealed smaller luminal areas and thicker walls accompanied by moderately improved cardiac function after acute stress induction. Whole-exome deep gene-sequencing from isolated heart tubes revealed phenotype-corresponding changes in longevity-promoting and myotropic genes. We also found changes in genes controlling mitochondrial biogenesis and respiration. Analysis of mitochondrial respiration from whole flies revealed improved efficacy of ATP production with reduced electron transport-chain activity. Finally, we analyzed posttranslational modification of H3S28 in an experimental heart failure model and observed increased H3S28 phosphorylation levels in HF hearts. Our data establish a critical role of H3S28 phosphorylation in vivo for life span, stress resistance, cardiac and mitochondrial function in Drosophila. These findings may pave the way for H3S28 phosphorylation as a putative target to treat stress-related disorders such as heart failure.
Gesehen am 02.04.2020